Analisis Nilai Tambah Se'i Babi di KPTT Salatiga - Wijaya, Gunady; Sunaryanto, Lasmono Tri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The pig farming business in KPTT started in 2017, with renovations carried out to increase the productivity of raw meat. Despite the success of achieving an abundance of meat, challenges arose due to the lack of interest in raw pork, resulting in sales difficulties. Therefore, there is a need for processing into processed products to add value. The sale of piglets is still done online, and the production process using simple tools affects the production of piglets. To develop a business, SWOT analysis is needed to identify things that need to be developed. The purpose of this research is to determine the strategy for the development of pig meat in KPTT Salatiga and to evaluate the added value of raw pork meat into pig meat. The results of the research show that the added value per pig is Rp 55,300 per kilogram, with a value added ratio of 34%. The development strategy involves innovative collaboration of food manufacturers, strategic location marketing, and environmental cleanliness to increase consumer confidence.